2012
DOI: 10.1371/journal.pone.0029914
|View full text |Cite|
|
Sign up to set email alerts
|

Persistence of Borrelia burgdorferi in Rhesus Macaques following Antibiotic Treatment of Disseminated Infection

Abstract: The persistence of symptoms in Lyme disease patients following antibiotic therapy, and their causes, continue to be a matter of intense controversy. The studies presented here explore antibiotic efficacy using nonhuman primates. Rhesus macaques were infected with B. burgdorferi and a portion received aggressive antibiotic therapy 4–6 months later. Multiple methods were utilized for detection of residual organisms, including the feeding of lab-reared ticks on monkeys (xenodiagnosis), culture, immunofluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
218
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 197 publications
(226 citation statements)
references
References 55 publications
7
218
0
1
Order By: Relevance
“…such as by losing key genetic elements, "encysting," or changing morphology to round bodies (11,14,28,29). We used a ceftriaxone concentration of 15 g/ml to replicate the minimum drug level achieved in serum when the standard dose of 2 g intravenously (i.v.)…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…such as by losing key genetic elements, "encysting," or changing morphology to round bodies (11,14,28,29). We used a ceftriaxone concentration of 15 g/ml to replicate the minimum drug level achieved in serum when the standard dose of 2 g intravenously (i.v.)…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that B. burgdorferi may be sequestered in protective niches during animal infection such that antibiotics might be less effective (11,12,41). On the other hand, it is also possible that the host's immunologic response and/or other inhibitory factors found in vivo could result in a more rapid decrease in viability after exposure to an antibiotic than occurs after the same level of antibiotic exposure during in vitro cultivation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study in the primate model of Lyme borreliosis reported detection of spirochetes after antibiotic therapy, a conclusion that should be interpreted with caution (33). Subtherapeutic antibiotic levels were documented in experimental animals and measures of infection in the control sham-treated monkeys were not sufficiently robust to distinguish between inadequate treatment and the persistence of a subpopulation with antibiotic tolerance.…”
Section: Figurementioning
confidence: 97%